Transition to selective dry cow therapy for responsible antimicrobial use in dairy cattle: a case study - B. Contiero; G. Cozzi; I. Lora; F. Gottardo (Animal)
Antimicrobial resistance is a major concern for public health, requiring a collective effort towards reduced antimicrobial use (AMU) across society. Major AMU in dairy cows is addressed to prevent or treat mastitis. The drying-off represents a critical time for AMU as administering antimicrobials to all quarters of all cows (blanket dry cow therapy - BDCT) is still the most adopted strategy in many countries. To reduce AMU, the European Union (EU) has banned BDCT since January 2022, and farmers were challenged to switch to selective dry cow therapy (SDCT) protocols, which entail antimicrobial treatment only to target cows with a higher risk of intramammary infection at dry-off. This study provided an overview of the practices used by Italian dairy farmers to dry off the cows when the new EU Regulation on AMU came into force. The aim was to identify the efforts required for the transition to SDCT and identify targeted actions to facilitate its success that could be applied in countries where BDCT is still allowed. An extensive survey was carried out between January and March 2022 involving 810 dairy herds rearing more than 61 000 cows. The results showed that 67% of the farmers (60% of the cows) have already adopted dry cow treatment protocols that eliminated or significantly reduced the antimicrobial therapy, whereas the remaining part still used BDCT. In SDCT farms, the mean proportion of cows receiving intramammary antimicrobials at dry-off was 43%. The SDCT farms were generally smaller in size than BDCT ones, and many SDCT farmers seemed to pay more attention to a careful management of the cows at drying-off, combining a reduced milking frequency with a change in the feeding regime to lower milk yield. The SDCT farmers most commonly used individual cow somatic cell count data to identify animals that have to receive intramammary antimicrobials at dry-off, and they declared >300 000 cells/ml the most common threshold above which a cow was targeted for antimicrobial treatment. The survey highlighted that the Italian dairy sector had already made efforts to reduce AMU at dry-off when the new EU regulation started. However, about one-third of the surveyed farms still adopted BDCT, and SDCT protocols were not well codified among different farms. Therefore, further refinements of the selection criteria for treatment allocation, supported by specific farmers’ education and training, are needed to promote a responsible AMU at the dry-off of dairy cows.